Influ-activism: Outlining a New Area of Investigation Between Media Studies and Activism Research - Murru, Maria Francesca; Pedroni, Marco; Tosoni, Simone (Mediascapes journal, 2024)
In recent years, the convergence of activist and influencer practices has given rise to what we term “influ-activism”. This contribution seeks to define influ-activism as a dynamic hybrid space where digital activism and influence culture intersect, creating novel dynamics and challenges for both arenas. Influ-activism encompasses the marketing strategies and aesthetics typical of influencers, now employed by activists, as well as the political stances increasingly adopted by mainstream influencers. This convergence significantly impacts the visibility, authenticity, and mobilisation potential of social causes in the digital public sphere. The article unfolds in four main sections. The first section anchors influ-activism within the distinct literatures of influence culture and digital activism, providing a genealogy of the phenomenon and developing theoretical concepts for its understanding. The second section delves into the current literature on influ-activism, exploring the blending of influencer and activist practices. The third section offers a comprehensive methodological approach for the empirical study of influ-activism, examining its communicative agents, practices, audiences, and ecosystems. Finally, the conclusion considers the broader implications of influ-activism for the digital public sphere and suggests avenues for future research. By critically examining the neoliberal and platform logics that underpin influ-activism, this essay seeks to enhance the understanding of the intricate dynamics shaping contemporary digital activism and the broader influence culture.